Theories of Reasoned Action and Planned Behaviour for Predicting the Intention to Participate in Continuing Professional Education among Government Auditors - Ahmad, Masiah (2006)
Continuing Professional Education (CPE) is a primary vehicle through which professionals acquire, increase, maintain, improve and enhance professional competence and as a lifelong education in their career life. CPE improves government auditors’ knowledge and refines their auditing skills, allowing them to meet the challenges of a complex and ever-changing audit environment. It enhances the auditors’ proficiency and helps to ensure the quality of audits, as the issue of professional accountability is crucial to them. This is a prediction model study on the government auditors’ intention to participate in CPE within the next three years. The study tested the utility of the Theory of Reasoned Action (TRA), Theory of Planned Behaviour (TPB) and Bandura’s Self- Efficacy Theory in predicting the intention to participate in CPE. This study examined whether variables of attitude, subjective norms, perceived behavioural controls and self-efficacy, as well as age and educational attainment predicted the auditors’ intentions to participate in CPE. A stratified random sampling was used to select 404 auditors of the National Audit Department. Data were gathered using group administered and mail questionnaires. Three hundred and seventy three auditors or 92% of them completed and returned the survey questionnaires in this study. Pearson’s correlational analysis showed that attitude, subjective norms, perceived behavioural controls, self-efficacy, age, and educational attainment were significantly related with the auditors’ intentions to participate in CPE. The auditors showed a moderate to high level of intentions to participate in CPE. They preferred short courses and continuing education. The auditors indicated significant positive attitudes toward intention to participate in CPE. They perceived the importance of CPE factor as the highest attitude factor that influenced their participation in CPE. Subjective norms moderately influenced their intentions to participate in CPE. Subjective social norms have a higher correlation than subjective personal norm. The auditors selected spouse, employer and professional association as the three most important persons who influenced their intentions to participate in CPE. Contrary to most studies, subjective norm was a better predictor than attitude. More than half of the auditors reported a relatively moderate level of perceived behavioural controls. Cost, CPE course attributes and multiple roles were the three perceived behavioural factors that constrained their intentions to participate in CPE. The auditors displayed a significant positive self-efficacy towards participating in CPE. Age has a moderate negative relationship with intention to participate in CPE. The younger group of auditors was more interested in continuing education whilst the older group of auditors preferred attending short courses.Hierarchical multiple regression analysis revealed that attitude, subjective norms and perceived behavioural controls as postulated by TPB and Bandura’s Self-Efficacy Theory as well as age were found to be predictive of the auditors’ intentions to participate in CPE. The TPB on its own explained 33 percent of the variance in intention to participate. Self-efficacy has improved the research model and it accounted for an additional three percent of the variance. The inclusion of age has further explained the auditors’ intention to participate in CPE by another three percent. The TPB, Bandura’s Self-Efficacy Theory and age together accounted for 39 percent of the variance in intention to participate in CPE. This study supported the explanatory and predictive utility of TPB as a reliable predictor of intention. It indicated the behaviour being studied was not under complete volitional control. All the hypotheses were supported except the hypothesis on educational attainment. The results of this study provided a number of theoretical and practical implications on participation in CPE. Several recommendations were suggested to increase the intention to participate in CPE. This study also highlighted the need for further research on the intention to participate in CPE by considering other predictors of participation and in other populations.